DEVELOPMENT OF T-VECTOR FOR DIRECT CLONING OF PCR PRODUCTS - Gritsenko , D.A.; Kenzhebekova , R.T.; Deryabina , N.D.; Galiakparov , N.N. (Eurasian Journal of Applied Biotechnology, 2016)
Thermostable enzymes that lack3′ to 5′ exonuclease activity are able to add deoxyadenosine residues to 3′-overhangs in PCR-amplified products, thereby allowing direct cloning of PCR products into T-vectors. A T-vector for cloning of amplified products was created by inserting two Eam1105I restriction sites in the multiple cloning site of the plasmid pGEM‑3zf(+). The ‘excess’Eam1105I restriction site within theβ-lactamase gene was deleted by point mutation while maintaining the amino acid sequence. Addition of a spacer (282 nucleotides) between the Eam1105I sites increased the cleavage efficiency of the enzyme. The developed T-vector reduces the time and cost for cloning PCR products as compared to other methods involvingT-vector preparation with enzymatic addition of deoxythymidine to 3′-ends, primer design with suitable restriction sites, and restriction enzyme digestion of PCR products. The developed vector was used to clone the open reading frames of different sizes of grapevine virus A.